The Effect of the Team Game Tournament Model on Negotiation Text Writing Skills: A Quasi-Experimental Study of Grade X Students at SMAN 6 Tangerang Regency - Rosa Aulia Fitri Siregar; Goziyah; Ariyana (Yayasan Ilomata, 2026)
This study examined the effectiveness of the Teams Games Tournament (TGT) learning model in improving the negotiation text writing skills of Grade X students at SMAN 6 Tangerang Regency. Writing negotiation texts is an important component of Indonesian language learning, requiring students to develop structured arguments, coherent ideas, and persuasive language. However, students often experience difficulties in organizing ideas and expressing arguments effectively in written form. This quantitative quasi-experimental study employed a nonequivalent control group design involving 66 Grade X students from intact classes. The experimental group was taught using the TGT learning model for several instructional meetings, while the control group received conventional instruction. Pre- and post-test writing tasks on negotiation texts were assessed using a rubric covering content relevance, text organization, argument development, language use, and writing mechanics. Data were analyzed using the Wilcoxon signed-rank test and the Mann–Whitney U test with IBM SPSS Statistics version 27. The results showed a statistically significant difference in post-test writing scores, with higher average scores in the experimental group. These findings suggest that the Teams Games Tournament learning model is associated with improved negotiation text writing skills in this school context. However, the results should be interpreted with caution due to limitations such as the single-school sample, relatively small sample size, intact class assignment without full randomization, and the absence of long-term observation. Further research involving broader samples and different educational contexts is recommended to strengthen the generalizability of these findings.